A Minuman Fungsional ‘Monjaredu’ ( Lemon Kunyit, Jahe Sereh Madu) Sebagai Terapi Komplementer Gangguan Reproduksi Pada Wanita Perimenopause Usia Dewasa Tengah - Nina Tresnayanti; Eka Maulana; Sri Kubillawati (Jurnal Ners, 2026)
Perimenopause is a transitional phase experienced by women approaching menopause, characterized by significant hormonal changes and various physical and emotional symptoms. These symptoms can affect a woman's quality of life. The functional drink ‘Monjaredu’ contains lemon, turmeric, ginger, lemongrass, and honey as herbs known in traditional medicine as natural ingredients that have various health benefits. The purpose of this study was to utilize local herbs available in Indonesia, which were formulated in predetermined doses with a pleasant taste to be given to middle-aged perimenopausal women experiencing reproductive disorders. It is hoped that the Monjaredu drink can be used as a complementary therapy for perimenopausal women experiencing reproductive disorders. Monjaredu can be used as a complementary therapy for perimenopausal women experiencing reproductive disorders. The research method used was a quasi-experiment with a one-group pre- and post-test design. Symptoms were identified by conducting an initial survey (pre-test), and the effect of the intervention was measured using the Greene Climacteric Scale (GCS) symptom assessment scale with a paired t-test. The results showed that the Monjaredu functional beverage was well-received by respondents, with the majority experiencing symptom improvement and a decrease in GCS scores to an average of 19.9. The P-value was 0.01. Conclusion: There is a significant effect of Monjaredu functional beverage (lemon, ginger, turmeric, lemongrass, honey) on the improvement of reproductive disorder symptoms. Recommendations for future researchers include utilizing and promoting Monjaredu beverage as complementary therapy for perimenopausal women experiencing reproductive dysfunction. Keywords: Monjaredu; Perimenopause; reproductive disorders; Greene's Climacteric Scale